Suitability of frames with intentionally eccentric braces as the seismic-force-resisting system of high-rise buildings - González Ureña, Andrés (2023)
The Frame with Intentionally Eccentric Braces (FIEB) is a novel seismic-force-resisting system (SFRS) that overcomes several of the limitations of the widely adopted Concentrically Braced Frame (CBF), namely those related to its high elastic stiffness and marginal inelastic stiffness. Recent numerical studies have shown that, in comparison to equivalent CBFs, low- and midrise FIEBs offer an improved structural response to earthquake loading at a reduced cost owing to their significant post-elastic stiffness and to the better control over the overstrength. Another presumed advantage of FIEBs is that the stability of tall buildings under seismic action could be ensured through design by selecting the eccentric braces so that their post-elastic stiffness at each storey at the expected displacement is greater than the negative geometric stiffness, thus preventing the overshooting of storey drift demands due to the P-Δ effects. Moreover, the fact that a portion of the cross-section of the bracing members remains in the elastic range as they engage in plastic energy dissipation provides the frame with partial self-centering capability, further enhancing its stability. In this article, the suitability of FIEBs as the SFRS of high-rise buildings is investigated. 40-, 30-, and 20-storey model buildings, located in Vancouver, BC, are designed employing a revision of a displacement-based design procedure previously developed by the authors, and their seismic performance is assessed numerically through Non-Linear Response History Analysis (NLRHA). The results show that the so designed FIEBs exhibit a satisfactory response to ground motions, including those from long duration subduction earthquakes, suggesting that the FIEB system is indeed adequate for use in high-rise buildings.